Helicobacter pylori antimicrobial resistance and antibiotic consumption in the low‐resource Central America setting. Issue 4 (20th May 2019) - Ortiz, Vivian; Estevez‐Ordonez, Dagoberto; Montalvan‐Sanchez, Eleazar; Urrutia‐Argueta, Samuel; Israel, Dawn; Krishna, Uma S.; Romero‐Gallo, Judith; Wilson, Keith T.; Peek, Richard M.; Dominguez, Ricardo; Morgan, Douglas R.
Abstract: Background: Antimicrobial resistance is a global public health problem, particularly in low‐ and middle‐income countries (LMICs), where antibiotics are often obtained without a prescription. H. pylori antimicrobial resistance patterns are informative for patient care and gastric cancer prevention programs, have been shown to correlate with general antimicrobial consumption, and may guide antimicrobial stewardship programs in LMICs. We report H. pylori resistance and antimicrobial utilization patterns for western Honduras, representative of rural Central America . Methods: In the context of the western Honduras gastric cancer epidemiology initiative, gastric biopsies from 189 patients were studied for culture and resistance patterns. Antimicrobial utilization was investigated for common H. pylori treatment regimens from regional public (7 antimicrobials) and national private (4 antimicrobials) data, analyzed in accordance with WHO anatomical therapeutic chemical defined daily doses (DDD) method and expressed as DDD/1000 inhabitants per day (DID) and per year (DIY). Results: H. pylori was successfully cultured from 116 patients (56% males, mean age: 54), and nearly all strains were cagA + and vacAs1m1 + positive (99% and 90.4%, respectively). Unexpectedly, high resistance was noted for levofloxacin (20.9%) and amoxicillin (10.7%), while metronidazole (67.9%) and clarithromycin (11.2%) were similar to data from Latin America. Significant associations with age, gender, or histology were not noted, with the exception of levofloxacin (28%, P  = 0.01) in those with histology limited to non‐atrophic gastritis. Total antimicrobial usage in western Honduras of amoxicillin (17.3 DID) and the quinolones had the highest relative utilizations compared with other representative nations. Conclusions: We observed significant H. pylori resistance to amoxicillin and levofloxacin in the context of high community antimicrobial utilization. This has implications in Central America for H. pylori treatment guidelines as well as antimicrobial stewardship programs.